2008
DOI: 10.1509/jmkg.72.6.98
|View full text |Cite
|
Sign up to set email alerts
|

Customer Equity Drivers and Future Sales

Abstract: Research on linking operational marketing inputs to customer attitudes and customer behavior has been gaining significance concomitant with the growing recognition that customers are market-based assets. In response to this, researchers and practitioners have proposed several conceptual models. Despite recent advances in research, the results are still inconclusive as to the relationship between customer attitude and future sales. A reason for this could be due to the paucity of studies combining survey-based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
259
2
31

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 261 publications
(313 citation statements)
references
References 86 publications
21
259
2
31
Order By: Relevance
“…On the other hand, the results are inconsistent with the research of V. Vogel et al (2008). As past research shows that value equity is of primary importance of loyalty intentions and future sales in retail market (Vogel et al, 2008), our results states that offering low prices, improving convenience and quality of finance services is not as important while maximizing loyalty in banking sector.…”
Section: Discussioncontrasting
confidence: 97%
See 1 more Smart Citation
“…On the other hand, the results are inconsistent with the research of V. Vogel et al (2008). As past research shows that value equity is of primary importance of loyalty intentions and future sales in retail market (Vogel et al, 2008), our results states that offering low prices, improving convenience and quality of finance services is not as important while maximizing loyalty in banking sector.…”
Section: Discussioncontrasting
confidence: 97%
“…As past research shows that value equity is of primary importance of loyalty intentions and future sales in retail market (Vogel et al, 2008), our results states that offering low prices, improving convenience and quality of finance services is not as important while maximizing loyalty in banking sector. Banks must focus the attention on developing and maintaining favourable brand equity.…”
Section: Discussionmentioning
confidence: 48%
“…With respect to individual characteristics, the model includes gender (Mittal and Kamakura 2001), age (Homburg and Giering 2001), and income (Seiders et al 2005) as covariates. Prior studies have suggested that customers' consumption characteristics are important determinants of customer loyalty in consumer markets (Rust et al 2004;Vogel, Evanschitzky, and Ramaseshan 2008). Thus, relationship length (Verhoef 2003) is also included as a control variable.…”
Section: Control Variablesmentioning
confidence: 99%
“…VdU's customer satisfaction ratings were high, but it was the MD's view that customer satisfaction is not enough to ensure customer loyalty and that customers buy products and services at all the company's departments. The MD's view that customer satisfaction does often not lead to customer loyalty is also confirmed in the academic marketing literature (see, for example, Kumar, 2003, 2005;Tsao 2013;Vogel et al, 2008).…”
Section: Case Setting the Start Of The Project And Research Objectivesmentioning
confidence: 84%